2022
DOI: 10.1590/fst.105321
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effect of nisin and reuterin on methicillin-resistant Staphylococcus aureus (MRSA) and S. aureus ATCC 25937

Abstract: Nisin and reuterin are used in processed foods as preservatives. They are considered to be potential sources of natural antibiotics for the treatment of food contaminated by antibiotic-resistant bacteria, such as methicillin-resistant Staphylococcus aureus. We try to compare the best effect of both nisin and reuterin on the growth of methicillin-resistant S. aureus (MRSA) and S. aureus ATCC 25923. The results indicated that nisin at different concentrations inhibited the growth of methicillin-resistant S. aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…However, it should be noted that there are conflicting data regarding certain bacteria. On the one hand, the antimicrobial efficacy of nisin against the entire genus Staphylococcus is reported, on the other hand, there is evidence of its selective activity against representatives of this genus (e.g., nisin exhibits bacteriostatic activity against MRSA and does not inhibit the growth of S. aureus ATCC 25937) [4,5,9,13,27,[32][33][34][35][36]. Gram-negative bacteria are usually much less sensitive or resistant to nisin.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that there are conflicting data regarding certain bacteria. On the one hand, the antimicrobial efficacy of nisin against the entire genus Staphylococcus is reported, on the other hand, there is evidence of its selective activity against representatives of this genus (e.g., nisin exhibits bacteriostatic activity against MRSA and does not inhibit the growth of S. aureus ATCC 25937) [4,5,9,13,27,[32][33][34][35][36]. Gram-negative bacteria are usually much less sensitive or resistant to nisin.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Nisin has attracted considerable attention due to its broad spectrum of antimicrobial activity, low probability of developing bacterial resistance, and low cellular cytotoxicity at antimicrobial concentrations [5]. A number of studies have demonstrated antimicrobial and antibiofilm activity of nisin against multidrug-resistant S. pneumoniae, MRSA, multidrug-resistant P. aeruginosa, and vancomycin-resistant enterococci (VRE) [5,13,19,20,32,34,49,50]. Lipid II is also a molecular target for vancomycin, the glycopeptide antibiotic of the last resort treatment of infection caused by certain antibiotic-resistant gram-positive bacteria, including MRSA.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, there is no report on the resistance of pathogenic microorganisms to the reuterin system. Reuterin was considered to have a bactericidal effect on methicillin-resistant S. aureus [ 13 ]. Bennett et al [ 14 ] reported that reuterin was the most effective against multidrug-resistant bacteria causing bovine mastitis, compared with nisin, bactofein and pediocin.…”
Section: Potential Applications Of the Reuterin Systemmentioning
confidence: 99%
“…The antimicrobial mechanism of the reuterin system remains unclear due to the complexity and dynamic nature of the system. Nevertheless, the reuterin system exhibits a broad-spectrum antimicrobial activity against pathogens and spoilage organisms, including Gram-positive and Gram-negative bacteria, yeasts, fungi, protozoa, viruses [ 12 ] and even antibiotic-resistant bacteria [ 13 , 14 ]. Gram-negative bacteria are usually more sensitive to the reuterin system than Gram-positive bacteria [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%